COMPARATIVE STUDY OF CROSS-PLY LAMINATED COMPOSITE MATERIALS AND EFFECT OF BUCKLING RESPONSE WITH AND WITHOUT CUTOUTS - Aljibori, Hakim S. Sultan; Alhabeeb, S. A.; Algelal, Hasan M. A.; Asim M. H., Wail (Journal of Applied Engineering Science, 2022)
In this work, finite element analysis has been done along with experimental test and conducted using numerical and experimental tests of the buckling response of quasi-static compressive loading of six layers woven cross-ply laminated composite material [0º/90º/0º] with centrally square and circular cutouts. The effect of cut-out shape and its size with a buckling load were obtained experimentally and numerically. Compression experiment has been performed by using INSTRON machine, and the experimentally obtained buckling loads are compared with a numerical results obtained by ANSYS simulation program. Both experimental and numerical results are showing good agreement. It is noticed that the buckling load of the composite plate has been decreased with the increasing of the size of cutout. The cutout area, cutout ratio (d/w), fiber weight, plate thickness and fiber type of the plate has a major effect to the load of the cross-ply laminated composite plates.
Keywords: cut-out, composite plate, buckling load, compression and cross-ply laminated